Neurotoxic effects of rotenone and deltamethrin prolonged exposure on adult zebrafish - Jacopo Grisotto; Shima Tavakolian Haghighi; Atena Poor Sasan; Serena Pedron; Matteo Brunelli; Ugo Moretti; Giovanna Paolone (Scientific Reports)
Abstract The presence of pesticides in aquatic ecosystems has become an increasing concern. Contamination of ground and surface water results from substances escaping wastewater treatment plants (WWTP) and leaching from soil. Pesticides pose a significant threat to the aquatic environment, as even trace concentrations can damage the central nervous systems (CNS) of animals and humans. Rotenone (ROT), an electron transport chain inhibitor, causes selective dopaminergic (DA) degeneration, while deltamethrin (DM), a widely used type II pyrethroid insecticide, is known for its neurotoxic effect. We assessed the impact of chronic exposure to ROT (2 µg/L, 4 weeks) and DM (1 and 2.5 µg/L, 15 days) on the central nervous system of adult zebrafish. TUNEL assay analysis (n = 15 in total) revealed both pesticides triggered cell death in different brain regions of fish, including areas involved in sensory, motor, and cognitive processes. DM additionally affected regions associated with complex behaviors such as learning, memory, and decision-making. Immunohistological analyses (n = 12 in total) showed loss of DA neurons in the areas involved in the motor control of animals exposed to both pesticides. These neurotoxic effects were further supported by behavioral changes (n = 38 in total) in the Novel Tank Test (NTT), indicating alterations in movement and anxiety-like behavior. Our findings confirm that chronic sub-threshold exposure to chemicals present in environmental waters causes significant damage to cerebral tissue, leading to apoptosis and behavioral alterations.